CHARGE COMPONENTS OF INDUCTIVE EFFECT OF ALKYL GROUPS AND THEIR INFLUENCE ON THE CHEMOSELECTIVITY OF ALCOHOLS BENZOYLATION (Proceedings of the YSU B: Chemical and Biological Sciences, 2016)
The inductive effect of alkyl groups of alcohols is an additive quality, which arises because of the differences in electronegativities of atoms of hydrogen, carbon, and oxygen in the molecule of alcohol are provided. Thanks to that a negative charge is formed on carbon atoms of the C–H bond, and a positive charge on carbon atoms of C–O bond. We show that these charges are equivalent to the natural forces of affinity, which cause the chemoselectivity of molecules.
Keywords: electronegativity, chemoselectivity of molecules, acid of Pauling, base of Pauling